Dialogue - Latack, Janina C.; Kinicki, Angelo; Prussia, Gregory E.; Wekselberg, Victor; Tinsley, Dillarad B.; Schoorman, F. David; Mayer, Roger C.; Davis, James H.; Davis-Blake, Alison; Pfeffer, Jeffery; Shane, Scott A.; Herold, David M.; et al. (Academy of Management Review, 1996)
This article presents a series of editorials in response to articles published in the issue as well as in previous issues, including the article “Negative affectivity and coping with job loss,” by J. M. George and A. P. Brief and “An integrative model of organizational trust,” by R. C. Mayer, J. H. Davis, and F. D. Schoorman. Topics of discussion include organizational behavior, industrial management, executive ability, and professional ethics.